If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + 4) = 0 Reorder the terms: -5(4 + t) = 0 (4 * -5 + t * -5) = 0 (-20 + -5t) = 0 Solving -20 + -5t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -5t = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -5t = 0 + 20 -5t = 0 + 20 Combine like terms: 0 + 20 = 20 -5t = 20 Divide each side by '-5'. t = -4 Simplifying t = -4
| x+0.09x=1015.88 | | 12x-29=91 | | 2x-1=12x-121 | | 4w^2-9=0 | | 13d+2722d=3d | | 5(x+1)=7-2(5x+8) | | X^4-8x^3+23x^2-28x+12=0 | | 9x-(2x+21)=21 | | a^2-10d^2=-38 | | 5(x-3)-10=0 | | 10+7p=8p | | 7x-5=8(x+3) | | 4x+9=2x+3 | | 6y+7=5y-1 | | 4x+3=2x+3 | | 17x-(8x-9)=36 | | 4x+10=-88-10x | | 0.7+y=-1.34 | | 4(x-3)=3(2x-1) | | 6a-2b+5b= | | 2x^2=0 | | 7(2x+3)+6(x-2)=10x+2 | | 4x-5=7x | | 0=3x | | X^4-5x^2-12=0 | | 4x+2(23-x)=70 | | 110-5x=13x+16 | | 4x+2(X+1)=32 | | 4x+9=-30-9x | | 99-3x=4x+22 | | 31-16=5(x-3) | | 5(3x-4)=4(2x+9) |